Psychomyiidae - Küçükbasmaci, İbrahým; Canbulat, Savaş (Zenodo, 2020)
Published as part of Küçükbasmaci, İbrahým & Canbulat, Savaş, 2020, A List of the Caddisflies (Insecta: Trichoptera) from Kyrgyzstan, with a New Record (Triaenodes reuteri McLachlan 1880), pp. 113-122 in Zootaxa 4896 (1) on page 115, DOI: 10.11646/zootaxa.4896.1.6, http://zenodo.org/record/4359410

Family Psychomyiidae Tinodes turanicus Martynov 1927 —Range: Uzbekistan, Kazakhstan, and Kyrgyzstan (Kučinić et al. 2016; Morse 2020; Smirno-va et al. 2016).
Keywords: Insecta; Arthropoda; Trichoptera; Animalia; Psychomyiidae; Biodiversity; Taxonomy